The clinical significance of manual microscopy in resolving automated haematology discrepancies: a case study of familial Pelger-Hüet anomaly - Giorgi Tkeshelashvili (Georgian Medical Journal, 2026)
Background: Automated haematology analysers classify leucocytes based on quantitative parameters of volume, conductivity, and light scatter. However, this design cannot interpret certain benign hereditary nuclear variants. Pelger-Hüet anomaly (PHA), a hereditary, autosomal-dominant condition arising from mutations in the lamin B receptor (LBR) gene, is frequently misclassified by such platforms as a pathological left shift, since its hyposegmented and densely condensed nuclei present a reduced scatter complexity resembling that of immature band forms. Case presentation: This case study documents a familial cluster of PHA in two siblings evaluated in Tbilisi, Georgia, with a reported paternal history of the same trait consistent with autosomal-dominant transmission. Peripheral blood smears from both patients were prepared using the standard wedge technique, stained with Wright-Giemsa, and evaluated under oil-immersion microscopy. One hundred neutrophils per patient were classified by nuclear lobe number and chromatin architecture. Results: Patient 1 showed 94% hyposegmented neutrophils (87% bilobed, 7% monolobed) and Patient 2 showed 96% (91% bilobed, 5% monolobed). The automated five-part differential did not report an independent hyposegmented neutrophil or PHA category for either sample; instead, affected cells were distributed across the neutrophil and band-form channels without a distinguishing flag. Conclusion: Manual smear evaluation, through assessment of chromatin condensation, nuclear architecture, and cytoplasmic maturity, remains necessary to differentiate benign hereditary PHA from false left-shift misclassification and from the acquired pseudo-Pelger-Hüet anomaly associated with myelodysplastic and malignant myeloid processes. Manual smear review following an automated left-shift flag should be regarded as a primary diagnostic procedure, not a supplementary step. Keywords: Pelger-Hüet anomaly; lamin B receptor; neutrophil morphology; automated haematology analyser; left shift; peripheral blood smear; Wright-Giemsa; manual microscopy; band form; hyposegmentation